KAJIAN SUHU PERMUKAAN LAUT BERDASARKAN DATA CITRA SATELIT NOAA-AVHRR DAN DATA ARGO FLOAT DI PERAIRAN SELATAN JAWA - Akhbar, Ade Imam; Jaya, Yales Veva; Febrianto, Try (Dinamika Maritim, 2018)
Sea surface temperature is one of the important oceanographic parameters, sea surface temperature in the southern sea of Java, including one of the sea that get the influence of the monsoon system which causes sea surface temperatures in the southern sea of Java are always changing. The aim this study was to determined sea surface temperature in southern sea of Java based on NOAA-AVHRR image data analysis and Argo Float analysis, the difference in sea surface temperature from NOAA-AVHRR image data with Argo Float. This research was conducted with image processing method from 7 NOAA-AVHRR image data of type level 1B, processed sea surface temperature algorithm by McMillin & Crosby. Argo Float is processed with Ocean Data Software View Version 4.7.3. to get temperature profile and the top layer temperature is assumed be sea surface temperature from Argo Float. The results of this study indicate the value of sea surface temperature from NOAA-AVHRR image is lower than Argo Float data with a difference of 1.01 Â° C to 1.41 Â° C at 7 observation data.